Study on the Relationship Between the Expression of B Cell Mature Antigen and the Classification, Stage, and Prognostic Factors of Multiple Myeloma - Ma, Tiantian; Shi, Jing; Xiao, Yuxia; Bian, Tianyue; Wang, Jincheng; Hui, Lingyun; Wang, Mengchang; Liu, Huasheng (Frontiers in Immunology, 2021)
The expression level of BCMA in bone marrow of 54 MM patients was detected in this study to explore the relationship between the BCMA expression and the classification, stage and prognostic factors of MM. The BCMA expression level of the stable group and remission group was lower than that of the newly diagnosed group and relapse group（P=0.001）.There was no significant difference in BCMA expression of MM patients in different types and stages (P>0.05), but it was found that for the newly diagnosed MM patients, the BCMA expression level of IgG patients was higher than that of IgA or light chain patients (rank average 11.20 vs 5.44, P=0.014). There was no significant correlation between the BCMA expression and the age and serum creatinine of MM patients(P>0.05). And there was no significant difference in BCMA expression between patients with different levels of age and serum creatinine(P>0.05). But it was found that the BCMA expression level of the newly diagnosed MM patients was moderately positively correlated with their age(P=0.025,r=0.595). There was no significant correlation between the BCMA expression and serum β2-microglobulin, serum lactate dehydrogenase, free kap/lam ratio, and urine β2-microglobulin(P>0.05). But we found that the BCMA expression of patients with high serum β2-microglobulin was higher than that of patients with low serum β2-microglobulin (rank average 28.89 vs 17.54, P=0.017).And the BCMA expression of patients with abnormal serum free kap/lam ratio was higher than that of patients with normal ratio (rank average 28.49 vs 13.55, P=0.004). The BCMA expression was strongly positively correlated with 24-hour urine protein, and was moderately positively correlated with serum M protein and the percentage of plasma cells in bone marrow, and was moderately negatively correlated with albumin and hemoglobin count, and was weakly positively correlated with serum corrected calcium(P<0.05). And it was found that the BCMA expression of positive serum immunofixation electrophoresis patients was higher than that of negative patients(rank average 29.94 vs 16.75, P=0.017). And we try to clarify the relationship between the bone marrow BCMA expression and the peripheral blood sBCMA expression. However, we have not found a clear correlation between them so far(P>0.05).